Cardiac sympathetic burden reflects Parkinson disease burden, regardless of high or low orthostatic blood pressure changes - Sang-Won Yoo; Joong-Seok Kim; Yoon-Sang Oh; Dong-Woo Ryu; Seunggyun Ha; Ji-Yeon Yoo; Kwang-Soo Lee (npj Parkinson's Disease, 2021)
Abstract Reduced uptake of 123I-meta-iodobenzylguanidine (123I-MIBG) and orthostatic hypotension (OH) are independently associated with worse clinical outcomes of Parkinson’s disease (PD). However, their interactive influence on PD has not been studied. The role of 123I-MIBG myocardial uptake, as a biomarker of PD severity, was investigated, conditional on the mediating effects of OH. A total of 227 PD patients were enrolled. Their motor and nonmotor aspects were assessed with standardized tools. Global disease burden was estimated by averaging the scaled z-scores of the assessment tools. Every patient went through 123I-MIBG scan, and OH was evaluated with the head-up tilt-test. The mediating role of orthostatic blood pressure changes (ΔBP) on the association between cardiac sympathetic denervation and disease burden was investigated. Low heart-to-mediastinum (H/M) ratio with less than 1.78 was seen in 69.6% of the patient population, and 22.9% of patients had OH. Low H/M ratio was associated with OH, and these patients had worse disease burden than subjects with normal 123I-MIBG uptake (global composite z-score: normal 123I-MIBG vs. abnormal 123I-MIBG; −0.3 ± 0.5 vs. 0.1 ± 0.7; p < 0.001). The mediation models, controlled for age and disease duration, revealed that the delayed H/M ratio and global composite score were negatively associated, irrespective of orthostatic ΔBP. Adverse relationship between cardiac sympathetic denervation and disease burden was shown without any interference from orthostatic blood pressure fluctuations. This result suggested that extracranial cardiac markers might reflect disease burden, regardless of labile blood pressure influence.